2009
DOI: 10.1007/s00404-009-1283-x
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal tuberculosis in premenopausal patients with elevated serum CA 125

Abstract: Increased CA 125 levels should be evaluated carefully prior to aggressive surgical approach, especially in premenopausal women and frozen section evaluation should be done before extensive surgical procedure if there is any suspicion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…Abdominal tuberculosis predominantly involves the younger age population as evident with third decade being the most commonly affected. This correlates well with other national and international studies [7][8][9][10][11][12].…”
supporting
confidence: 91%
“…Abdominal tuberculosis predominantly involves the younger age population as evident with third decade being the most commonly affected. This correlates well with other national and international studies [7][8][9][10][11][12].…”
supporting
confidence: 91%
“…However, a number of studies have shown increased CA-125 levels in cases of intestinal TB [26,40], and some studies have demonstrated an increased ESR in TB [10,26,30,36,38,41]. High ESR, as determined in the two cases presented in this study, declined to normal levels at the end of treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Although we had no opportunity to assay serum CA-125 level, which is not readily available in our environment, use of CA-125 in discriminating metastatic ovarian cancer from other disease conditions is extremely difficult. CA -125 a tumour associated antigen is no specific, as it is elevated in a variety of conditions including TB [ 12 ]. We also had no opportunity of assaying Ascitic fluid adenosine deaminase (ADA), Omental biopsy and peritoneal was also not done to rule out involvement of the peritoneum.…”
Section: Discussionmentioning
confidence: 99%